Formaldehyde Induces Mesenteric Artery Relaxation via a Sensitive Transient Receptor Potential Ankyrin-1 (TRPA1) and Endothelium-Dependent Mechanism: Potential Role in Postprandial Hyperemia - Jin, L.; Jagatheesan, G.; Guo, L.; Nystoriak, M.; Malovichko, M.; Lorkiewicz, P.; Bhatnagar, A.; Srivastava, S.; Conklin, D. J. (Frontiers in Physiology, 2019)
Formaldehyde (FA), the smallest aldehyde, is generated endogenously, and is widespread in the environment in foods, beverages and as a gas phase product of incomplete combustion. The main metabolite of FA, formate, was increased significantly in murine urine (∼3×) after overnight feeding. Because feeding increases mesenteric blood flow, we explored the direct effects of FA in isolated murine superior mesenteric artery (SMA). Over the concentration range of 30–1,200 μM, FA strongly and reversibly relaxed contractions of SMA induced by three different agonists: phenylephrine (PE), thromboxane A2 analog (U46,619) and high potassium (60K, 60 mM K+). Formate (to 1.5 mM) induced a modest relaxation. FA (>1,500 μM) irreversibly depressed vascular function in SMA indicating vasotoxicity. The sensitivity (EC50) but not the efficacy (% relaxation) of FA-induced relaxations was dependent on blood vessel type (SMA << aorta) and contractile agonist (PE, EC50= 52 ± 14 μM; U46,619, EC50= 514 ± 129 μM; 60K, EC50= 1,093 ± 87 μM). The most sensitive component of FA vasorelaxation was within physiological levels (30–150 μM) and was inhibited significantly by: (1) mechanically impaired endothelium; (2) Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME); (3) transient receptor potential ankyrin-1 (TRPA1) antagonist (A967079); (4) guanylyl cyclase (GC) inhibitor (ODQ); and, (5) K+ channel inhibitor (BaCl2). A similar mechanism of SMA vasorelaxation was stimulated by the TRPA1 agonist cinnamaldehyde. Positive TRPA1 immunofluorescent staining and gene-specific sequence were present in SMA but not in aorta. These data indicate FA, but not formate, robustly relaxes SMA via a sensitive TRPA1- and endothelium-dependent mechanism that is absent in aorta. Thus, as FA levels increase with feeding, FA likely contributes to the physiological reflex of post-prandial hyperemia via SMA vasodilatation.